Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Neuroprotection of exercise: P2X4R and P2X7R regulate BDNF actions - Bing-xin Sun; Ai-shi Peng; Pei-jie Liu; Min-jia Wang; Hai-li Ding; Yu-shi Hu; Liang Kang (Purinergic Signalling, 2023)
The neurotrophin brain-derived neurotrophic factor (BDNF), which acts as a transducer, is responsible for improving cerebral stroke, neuropathic pain, and depression. Exercise can alter extracellular nucleotide levels and purinergic receptors in central nervous system (CNS) structures. This inevitably activates or inhibits the expression of BDNF via purinergic receptors, particularly the P2X receptor (P2XR), to alleviate pathological progression. In addition, the significant involvement of sensitive P2X4R in mediating increased BDNF and p38-MAPK for intracerebral hemorrhage and pain hypersensitivity has been reported. Moreover, archetypal P2X7R blockade induces mouse antidepressant-like behavior and analgesia by BDNF release. This review summarizes BDNF-mediated neural effects via purinergic receptors, speculates that P2X4R and P2X7R could be priming molecules in exercise-mediated changes in BDNF, and provides strategies for the protective mechanism of exercise in neurogenic disease.

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Purinergic ATP triggers moxibustion-induced local anti-nociceptive effect on inflammatory pain model - Hai-Yan Yin; Ya-Peng Fan; Juan Liu; Dao-Tong Li; Jing Guo; Shu-Guang Yu (Purinergic Signalling, 2023)
Purinergic signalling adenosine and its A1 receptors have been demonstrated to get involved in the mechanism of acupuncture (needling therapy) analgesia. However, whether purinergic signalling would be responsible for the local analgesic effect of moxibustion therapy, the predominant member in acupuncture family procedures also could trigger analgesic effect on pain diseases, it still remains unclear. In this study, we applied moxibustion to generate analgesic effect on complete Freund’s adjuvant (CFA)-induced inflammatory pain rats and detected the purine released from moxibustioned-acupoint by high-performance liquid chromatography (HPLC) approach. Intramuscular injection of ARL67156 into the acupoint Zusanli (ST36) to inhibit the breakdown of ATP showed the analgesic effect of moxibustion was increased while intramuscular injection of ATPase to speed up ATP hydrolysis caused a reduced moxibustion-induced analgesia. These data implied that purinergic ATP at the location of ST36 acupoint is a potentially beneficial factor for moxibustion-induced analgesia.

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Roles of the lateral fenestration residues of the P2X4 receptor that contribute to the channel function and the deactivation effect of ivermectin - Chao Gao; Qiaqia Yu; Huijuan Xu; Longmei Zhang; Jingxin Liu; Yanling Jie; Wenbo Ma; Damien S. K. Samways; Zhiyuan Li (Purinergic Signalling, 2015)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)